(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Background: This study explores into the investigation of the impact of organisational elements on the performance of Saudi Arabian EMS in various contexts, including rural & urban areas. The current research aims to learn more about the organisational variables that may explain why EMS performance differs in urban or rural areas from the perspectives of frontline personnel. Method: Researchers in Saudi Arabia’s Riyadh region carried out the study. Participants were required to have worked for the Saudi Red Crescent EMS for at least 5 years and be currently engaged in one of the following roles: technician, paramedic, or EMS station manager. The first participants who responded to the call for participation were interviewed using semi-structured interviews from October 2021 to July 2022. The process proceeded until all data is acquire. We will analyse the data using analysis methodology. Results: Forty people from the Saudi Red Crescent EMS are a part of the final sample (20 from rural areas and 20 from urban centres). The data analysis is reveal important organisational characteristics that caused EMS staff to face obstacles & hurdles. There were also some similarities. Conclusion: Results showed that EMS performance is negatively affected in both urban & rural locations.